Clinical nurses' experiences of workplace verbal violence: a phenomenological study - Min Soo Woo; Hyoung Suk Kim; Jeung-Im Kim (Korean Society of Women Health Nursing, 2022)
Purpose This study aimed to describe clinical nurses' lived experiences of workplace verbal violence through qualitative research using descriptive phenomenology. Methods Six female Korean nurses who had less than 5 years of clinical experience and had experienced verbal violence in the workplace within the past year participated in the study. Data were collected through one-on-one in-depth interviews with the participants and analyzed using Colaizzi's phenomenological method. Results A total of 27 codes, eight themes, and four theme clusters were derived from the participants' statements. The four theme clusters of the clinical nurses' experiences of verbal violence in the workplace were as follows: "tip of the iceberg," "beyond me and my control," "fear and resignation," and "personal burden." The participants recognized that nurses experienced verbal violence daily, and that the causes of and responses to verbal violence were determined by external situational factors rather than nurses' individual problems. This suggests that nurses felt that they had no choice but to personally cope with verbal violence and bear the consequences due to systematic indifference and silence about verbal violence experienced by clinical nurses. Conclusion The findings show that verbal violence was pervasive and unmerited, yet often endured at the cost of a personal burden to nurses. A clear definition of verbal violence and education for employees are needed, and a reporting system should be established to report all forms of violence regardless of the severity of the incident.